PSYCHOANALYTIC DYNAMICS IN THE POEM AJMALU AL-HUBB BY MAHMOUD DARWISH FROM THE PERSPECTIVE OF SIGMUND FREUD: DINAMIKA PSIKOANALISA PADA PUISI AJMALU AL-HUBB KARYA MAHMOUD DARWISH PERSPEKTIF SIGMUND FREUD - Alwah Asaniah; Nushrotun Nida (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2024)
Mahmoud Darwish's poem Ajmalul Hubb is a literary work renowned for depicting the profound feelings of love, yet it also contains inner conflicts related to uncertainty and anxiety about the future. The poem reflects the complexity of human emotions, where love is not only seen as a romantic feeling, but is also affected by deep psychological upheaval. The purpose of this study is to identify the sentences in the poem Ajmalul Hubb by Mahmud Darwish that describe a love experienced. The data source of this research is Mahmud Darwish's Ajmalul Hubb poem. This research uses qualitative descriptive methodology. Data were collected through reading and note-taking, which involved understanding the correlation between theory and data, as well as categorising information based on the concepts of id, ego, and superego. The results of the study show that the poem is not only a linguistic aesthetic expression, but also a reflection of a deep psychological state, which can be understood through the lens of Freud's psychoanalytic theory. The findings may provide additional insights for the reader